Solar cell model: a bond graph approach. (April 2015) - Tapia-Sánchez, R; Medina-Rios, A; Villa-Villaseñor, N
A solar cell model that combines the photovoltaic and electro-thermal processes is proposed. The bond graph methodology is used as a reference frame, allowing the representation of the whole structure in a unified approach. The solar cell structure is modeled as a three-dimensional object allowing observation of a nonuniform solar radiation on the surface. Subsequently, the proposed model is used in the solar cell design.